The Effectivenes of E-Comic as A Learning Tool on Short Story Writing Among Elementary School Students - Bachtiar, Afakhrul Masub; Nurrohmah, Oktaviana; Yunita, Nourma (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
The results of the analysis show a comparison between two means of two paired samples with the assumption of normal distribution. Decision-making in the t-test focuses on the significance value (2-tailed). If the significance value (sig) is less than 0.05, in which case H0 is accepted and H1 is rejected, so there is a relevant difference between the initial and final variables, this also indicates a relevant effect of the different treatment of each variable. Conversely, if the sig (2-tailed) is greater than 0.05, where H0 is accepted and H1 is rejected, then there is no relevant difference between the baseline and endline variables, which also indicates that there is no relevant effect of the different treatments of each variable. There is an analysis result of the pre and post-test with a relevant value (2-tailed) of 0.00, which is smaller than 0.05, proving that there is a relevant difference between the two variables and there is an impact of the application of E-Comic media as a learning medium on the ability to write short stories